2020
DOI: 10.1007/s10340-020-01319-2
|View full text |Cite
|
Sign up to set email alerts
|

The selective sequestration of glucosinolates by the cabbage aphid severely impacts a predatory lacewing

Abstract: The cabbage aphid Brevicoryne brassicae is a notorious agricultural pest that specializes on plants of the Brassicaceae family, which are chemically defended by glucosinolates. By sequestering glucosinolates from its host plants and producing its own activating enzyme (myrosinase), this aphid employs a self-defense system against enemies paralleling that in plants. However, we know little about the metabolic fate of individual glucosinolates during aphid sequestration and activation and about the biochemical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
(53 reference statements)
1
11
0
3
Order By: Relevance
“…This result is consistent with those of other investigations in which, A. pisum did not feed on faba bean artificially infused with sinigrin, a glucosinolate [44,45]. Brevicoryne brassicae, another specialist aphid, is unaffected by the glucosinolate-myrosinase defense system of brassicas [46]. These results demonstrated that the sequestration of glucosinolates from host plants is speciesspecific and may have as-yet-unknown evolutionary implications.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with those of other investigations in which, A. pisum did not feed on faba bean artificially infused with sinigrin, a glucosinolate [44,45]. Brevicoryne brassicae, another specialist aphid, is unaffected by the glucosinolate-myrosinase defense system of brassicas [46]. These results demonstrated that the sequestration of glucosinolates from host plants is speciesspecific and may have as-yet-unknown evolutionary implications.…”
Section: Discussionsupporting
confidence: 92%
“…Negative effects of plant secondary metabolites on predation are well established, and have recently been confirmed using molecular manipulative approaches [19][20][21].…”
Section: Introductionmentioning
confidence: 94%
“…As many glucosinolates and isothiocyanates are released upon tissue damage by the glucosinolate–myrosinase system chewing insects are more affected compared to phloem-sucking insects. Phloem-sucking insects are able to avoid most contact with myrosinase by feeding from the phloem (Sun et al 2020 ), and some of them even sequester glucosinolates to use them against their enemies like the specialised cabbage aphid ( Brevicoryne brassicae ) (Kazana et al 2007 ). However, non-specialised aphid species like the green peach aphid M. persicae are affected by an increase in indol GSL levels in leaves of A. thaliana (Kim et al 2008 ).…”
Section: Breeding Targets Conferring Insect Resistancementioning
confidence: 99%